2021
DOI: 10.3390/rs13122293
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Lakes Surface Water Velocity with SAR: A Feasibility Study on Lake Garda, Italy

Abstract: The SAR Doppler frequencies are directly related to the motion of the scatterers in the illuminated area and have already been used in marine applications to monitor moving water surfaces. Here we investigate the possibility of retrieving surface water velocity from SAR Doppler analysis in medium-size lakes. ENVISAT images of the test site (Lake Garda) are processed and the Doppler Centroid Anomaly technique is adopted. The resulting surface velocity maps are compared with the outputs of a hydrodynamic model s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…The two LSWT time series (Figure 5b) are strongly correlated (0.906) and show a high NSE (0.906), and the RMSE of 1.745 • C is relatively small compared to the range of LSWT (standard deviation of ±5.75 • C from CCI-Lakes database). The latter tends to be 0.5 • C warmer than the simulated water temperature, which is consistent with what was observed by the authors during the calibration and validation of the model against remotely sensed data from multiple sensors datasets (e.g., Landsat8, AVHRR, MODIS-Aqua, see [35], MODIS-Terra, see [57]).…”
Section: Validation Of Lakevap Products With Delft3d Outputssupporting
confidence: 89%
See 1 more Smart Citation
“…The two LSWT time series (Figure 5b) are strongly correlated (0.906) and show a high NSE (0.906), and the RMSE of 1.745 • C is relatively small compared to the range of LSWT (standard deviation of ±5.75 • C from CCI-Lakes database). The latter tends to be 0.5 • C warmer than the simulated water temperature, which is consistent with what was observed by the authors during the calibration and validation of the model against remotely sensed data from multiple sensors datasets (e.g., Landsat8, AVHRR, MODIS-Aqua, see [35], MODIS-Terra, see [57]).…”
Section: Validation Of Lakevap Products With Delft3d Outputssupporting
confidence: 89%
“…In general, the different behavior of the two sub-basins results from the different ways they exchange heat through the water surface, which is a direct consequence of the different morphological characteristics as well as different atmospheric forcing. This also causes a typical surface temperature gradient, with the southern part of the lake being warmer than the northern part, which is visible from either in-situ data or remote sensing imagery [35,57,58].…”
Section: Study Sitementioning
confidence: 99%
“…Wind and wave erosion were always also likely to influence this zone given its location at the south of the lake and the prevailing northerly winds, coupled with a potential fetch of 50 km. The wind event in May 2019 was estimated using ERA5 data as no in situ data was available but estimated wave heights of 0.4 m were close to previous estimates on typical high-wind-speed days of 0.5 m [88]. The wind event is likely to have played a role in the loss of dense macrophytes in 2019, and local newspapers recorded the storm as causing substantial crop damage and felling trees.…”
Section: Discussionsupporting
confidence: 59%
“…This indicated that the influence of exposure to waves was one of the principal drivers (favoring the damage, breakage, or uprooting of macrophytes) as shallower areas of 3 m or less are often exposed to wave action [15,16]. In addition, the area to the west, partially in the lee of the head of the peninsula, had more macrophytes and experienced less loss, and recent models have indicated that this area may be more protected given the direction of wind vectors [88].…”
Section: Discussionmentioning
confidence: 99%
“…Natural disasters often occur due to recent climate changes. Several studies have focused on climate change and its' effect detection where Remote sensing methods are highly used in these methodologies [71].…”
Section: Introductionmentioning
confidence: 99%